PERILAKU BERWIRAUSAHA PENDUDUK MISKIN DALAM MELANGSUNGKAN KEHIDUPANNYA - Bahrin Bahrin; Duharman Duharman; Ade Irma Suryani (UM. Bengkulu, 2022)
This study aims to: (1) know the characteristics of poor households in Talang Kabu Village, Ilir Talo District, Seluma Regency, (2) know the level of fulfillment of basic needs, and (3) know the entrepreneurial behavior of the poor in Talang Kabu Village, Ilir Talo Kaupaten Seluma District. This research is designed as a qualitative descriptive research. The research location is in Talang Kabu Village, Ilir Talo District, Seluma Regency. Village selection is carried out on a Purposive basis, while the selection of samples of poor families is carried out randomly. Data collection using questionnaires, observations and in-depth interviews. Data analysis is carried out in a qualitative descriptive manner. Based on the results of research and discussion, it can be concluded that several things are as follows: (1) The characteristics of poor households in Talang Kabu Village are seen in terms of the age of the head of the family, generally between 40-50 years old,, the level of education is mostly finished elementary school, the average per capita income level per month is IDR 120,000,-, the number of family dependents of 5 or more as much as 60.00%, the number of family members who work is mostly only 2 people with a percentage of 72.73%.; (2) The level of meeting the basic needs of the household, the fulfillment of food needs are included in the sufficient category, the need for clothing as much as 93.73% do not have a change of clothes, and as many as 89.09% can only buy new clothes 1 time a year, the fulfillment of board needs is mostly feasible and already has their own house, if most of them are sick (96.36 %) seek treatment at the Puskesmas; and the fulfillment of the need for clean water as a whole falls into the category of sufficient.; (3) The entrepreneurial behavior of the poor in Talang Kabu Village generally they have made various efforts to fulfill their lives which include: rice fields with a percentage of 36.36%, oil palm plantations 12.73%, rubber plantations 34.55%, carpentry 5.45%, farm workers 60.00%, trade 34.55%, confidence level in carrying out business 76.36%, happy in carrying out business 72.72%, courage in taking risks 40%, entrepreneurship influenced by the environment 47.27%, and the importance of honesty in trying 90.91%. Keywords: Poverty, behavior, entrepreneurship